Simulation modeling for operations improvement at a leading banking hub - Jamin, Kong (2005)
This study focuses on the utilization of simulation software to model the process flow of a banking hub. It is aimed at analyzing whether the management's goal towards a better delivery standard is feasible, and if so, how it could be achieved. Statistical analysis is carried out to ensure that the model built could represent the actual scenario. Having proved such, an analysis of the current situation is done and weakness identified - enabling determination of whether that the management's goal bound by their defined constraints is feasible or not. Having proven that the goals are not achievable, further studies are carried out using What-If analysis and recommendations on other available options will be presented. Finally, future studies and recommendations on how the study could be better improved shall also be discussed